The Roles and Attributes of the Clinical Teacher that Contribute to Favourable Learning Environments: A Case Study from Physiotherapy - DV Ernstzen; Bitzer E (AOSIS, 2012)
The quality of clinical education is dependenton learning experiences. The clinical teacher plays a key role insuccessful clinical education.The aims of the study were to determine which roles and attributesof physiotherapy clinical teachers contribute to a supportiveclinical learning environment according to physiotherapy studentsand their clinical teachers.The study protocol was approved by the Committee for HumanResearch at Stellenbosch University. A qualitative research designwas used. An interview schedule was developed based on existing literature. Data was analyzed using contentanalysis. Data was coded, categorized and conceptualized into key themes and patterns.All third year (n=40) and fourth year (n=40) undergraduate physiotherapy students and their clinical teachers(n=37) were eligible to participate. Semi-structured individual interviews were conducted with a purposivesample consisting of six third-year students, six fourth-year students and six clinical teachers (n=18). Written informedconsent was obtained from all participants prior to the interviews.The teacher as role model and facilitator of learning was emphasised. The attributes of the clinical teacher thatcreated a supportive learning environment were approachability, recognising student abilities and good communicationskills. The value of active involvement and individualism in learning was highlighted.The study confirmed that the clinical teacher is pivotal in the success of a physiotherapy clinical education program.The findings agree with the large body of international literature about supportive clinical learning environments.